Kultura obywatelska w ponowoczesności. Wybrane konteksty edukacyjne - Czerwiński, Kazimierz (Studia Edukacyjne, 2020)
Civic culture can be understood as the orientation of citizens in public matters and broad social participation. Trust and cooperation as well as communication skills are also included in the components of this culture. In the conditions of social changes related to postmodernism, mainly such as: the appreciation of diversity, the growing importance of the media, the increase in the role of consumption, problems with identity, there is a need to redefine civic culture and its constitutive elements. This has significant implications for contemporary civic education.